Expression of the translocator protein (TSPO) from Pseudomonas fluorescens Pf0-1 requires the stress regulatory sigma factors AlgU and RpoH - Leneveu-Jenvrin, Charlène; Bouffartigues, Emeline; Maillot, Olivier; Cornelis, Pierre; Feuilloley, Marc G.; Connil, Nathalie; Chevalier, Sylvie (Frontiers in Microbiology, 2015)
The translocator protein (TSPO), previously designated as peripheral-type benzodiazepine receptor, is an evolutionary conserved protein that is found in many Eukarya, Archae and Bacteria, in which it plays several important functions including for example membrane biogenesis, signaling and stress response. A tspo homologue gene has been identified in several members of the Pseudomonas genus, among which the soil bacterium P. fluorescens Pf0-1. In this bacterium, the tspo gene is located in the vicinity of a putative hybrid histidine kinase-encoding gene. Since tspo has been involved in water stress related response in plants, we explored the effects of hyperosmolarity and temperature on P. fluorescens Pf0-1 tspo expression using a strategy based on lux-reporter fusions. We show that the two genes Pfl01_2810 and tspo are co-transcribed forming a transcription unit. The expression of this operon is growth phase-dependent and is increased in response to high concentrations of NaCl, sucrose and to a D-cycloserine treatment, which are conditions leading to activity of the major cell wall stress responsive extracytoplasmic sigma factor AlgU. Interestingly, the promoter region activity is strongly lowered in a P. aeruginosa algU mutant, suggesting that AlgU may be involved at least partly in the molecular mechanism leading to Pfl01_2810-tspo expression. In silico analysis of this promoter region failed to detect an AlgU consensus binding site; however, we detect a putative binding site for the heat shock response RpoH sigma factor. Accordingly, the promoter activity of the region containing this sequence is increased in response to high growth temperature and slightly lowered in a P. aeruginosa rpoH mutant strain. Taken together, our data suggest that P. fluorescens tspo gene may belong at least partly to the cell wall stress response.